Autonomy in normal delivery from the perspective of women assisted in birthing center - Adriana Lenho de Figueiredo Pereira; Amanda Domingos Bento (Rev Rene)
The purpose of this study is to describe the obstetric nursing care in normal childbirth and analyze the exercise of women’s autonomy during this care. It is a qualitative study carried out in the only birthing center in Rio de Janeiro. The interviews were conducted with postpartum women. The nurses’ care was described as satisfactory, with technical and human competencies, which includes the women’s needs, desires, expectations and choices in labor and delivery. Educational practices in prenatal assistance emerged as strategies care that allows the women to choose and making decisions over what is most appropriate for them. The obstetric nursing care in birthing center is based in the humanization, the integrality and practices care that promote the comfort, protagonism and autonomy during labor and delivery.